(untitled) (Development Service Industry Management, 2024)
The article examines the role of innovation in the development of enterprises. An approach to innovation management at an enterprise in the context of post-conflict transformation is developed, based on the premise that the goals of an enterprise should determine the goals of innovation management, and the processes of innovation management at an enterprise should be integrated with the vertical and horizontal levels of economic and production business processes in the context of post-conflict transformation. Based on the results of the study, the mathematical basis for innovation management in the system of methodological approaches (transfer management, algorithmic management, creative management) based on the identified processes of innovation management at enterprises in the context of post-conflict transformation is determined. An analysis of approaches to the formation of goals for managing innovations at enterprises in the context of post-conflict transformation is carried out. The approach, which is contained within 8 key spaces, with the allocation of 5 groups of goals (financial, production, marketing, human resource management, information and technical support) is substantiated. A system of goals for managing the innovation and investment activities of enterprise is formed. The author details managerial actions/decisions at the strategic, tactical and operational levels and specifies tactical functional goals in the context of financial, production, marketing, human resource management and information technology, which ensures further optimization of the use of various types of resources (primarily human resources) at the enterprise. A mathematical framework has been developed for the subsystem at the strategic, tactical and operational levels. The obtained results can be implemented in the activities of enterprises and used in further scientific research.